Al2O3–TiO2 Codoped Yttria‐Stabilized Zirconia Thermal Barrier Coatings Resistant to Damage by Molten Calcium‐Magnesium‐Alumino‐Silicate (CMAS) Glass. Issue 6 (9th March 2021) - Yuan, Ke; Yang, Li; Wang, Qiang; Zhang, Fan; Zhu, Wang; Zhou, Yichun
Abstract : Calcium‐magnesium‐alumino‐silicate (CMAS) corrosion is one of the main challenges for thermal barrier coatings applications. The main purpose of the current work is to investigate the CMAS resistance of doping of Al2 O3 –TiO2 codoped yttria‐stabilized zirconia (YSZ). Herein, the ceramic powders and pressed plates of YSZ doped with different Al2 O3 and TiO2 (referred to as ATYSZ) are prepared to determine the optimum composition. The results show that the YSZ doped with 10 mol% Al2 O3 and 5 mol% TiO2 (10A5TYSZ) can effectively resist the CMAS corrosion and has suitable thermal conductivity. Therefore, the coatings of 7YSZ and 10A5TYSZ are produced by using air plasma spraying (APS). The characteristics of 7YSZ and 10A5TYSZ coatings attacked by CMAS at 1250 °C are measured by scanning electron microscopy (SEM) and Raman spectra, which shows that the CMAS corrosion resistance of 10A5TYSZ coating is better than 7YSZ coating due to the formation of anorthite. The anorthite can increase the melting point of CMAS and block the penetration channel of CMAS, which can effectively prevent the further penetration of CMAS and alleviate the premature failure of TBCs. 10A5TYSZ is considered as a promising coating to improve the performance of CMAS resistance. Abstract : Calcium‐magnesium‐alumino‐silicate (CMAS) resistance of doping of Al2 O3 –TiO2 co‐doped yttria‐stabilized zirconia (YSZ) is investigated. The CMAS corrosion resistance of YSZ doped with 10 mol% Al2 O3 and 5 mol% TiO2 (10A5TYSZ) coating is better due to the formation of anorthite. The anorthite can increase the melting point of CMAS and block the penetration channel of CMAS.